Evaluation Of Pre-Evacuation Behavior Among Students And Staff In Engineering Campus, Universiti Sains Malaysia - Nazim, Muhamad Faiz Mohamad (Universiti Sains Malaysia, 2022)
This dissertation studies pre-evacuation behaviour among students and staff at the engineering campus of Universiti Sains Malaysia (USM), with an emphasis on how occupants at engineering campus, USM likely to react in the event of an emergency. According to the response of 185 genuine respondents, most of the residents grasp the situation and begin to evacuate themselves to a safer location when they hear the alert. As a result, some of them take a few seconds to ensure that they understand the circumstance they are in before acting. Besides aiming to study the pre-evacuation behaviour of the occupants, the demographic factors that influence the behaviour of the occupants also being studied. According to the data analysis using SPSS software, the test result demonstrated that gender had no influence on their pre-evacuation behaviour because there was no significant difference between females and males. However, the data revealed that occupants with prior experience and safety training influenced how they reacted during an emergency. After hearing the alarm, respondents tend to instantly evacuate the buildings and proceed to the assembly area. Furthermore, findings revealed no significant differences in age groups but not in educational background level. The occupants ignore the alarm and wait a few seconds instead of act accordingly. They also informed others once aware there is an emergency. Besides, they tend to call their family or friends to tell their current situation. The study's findings can help university administrators develop appropriate policies, design solutions, and training for efficient secure transfers. Aside from that, the results are a significant resource for constructing mathematical models and enhancing safety in educational institutions for safer evacuation of staff and students.